Institutional Philosophy on The Relationship of Language,Communication, and Islamic Literacy (The Spiral Andromeda Philosophy) - Kalayo Hasibuan; Adelia Purnawandira; Afri Yulianti; Aisyah Amini Zahara (Jurnal Pendidikan dan Sastra Inggris, 2025)
This paper explores the integration of English as a Foreign Language (EFL) instruction with Islamic perspectives through the Spiral Andromeda Philosophy developed by UIN Sultan Syarif Kasim Riau. Rooted in the principle of tauhid (oneness of Allah), this philosophical framework emphasizes the interconnectedness of natural sciences, social sciences, and Islamic studies. The study adopts a conceptual analysis method to examine how Islamic values, including ta'lim, tarbiyah, and ta'dib, can be embedded within EFL curriculum and pedagogy at various levels supra, macro, meso, and micro. By aligning language instruction with Quranic principles and Islamic ethics, particularly as reflected in QS. Fushshilat: 53, the approach aims to develop students who are linguistically proficient, spiritually aware, and ethically grounded. The findings highlight the potential of the Spiral Andromeda Philosophy to transform EFL classrooms into spaces for holistic education that nurture critical thinking, moral character, and intercultural communication based on Islamic values.